Impact of Crystalloid or Albumin Priming of the Heart–Lung Machine on Inhospital Outcome after Coronary Artery Bypass Surgery - Weiler, Pia; Hamiko, Marwan; Mellert, Fritz; Roell, Wilhelm; Roell, Martina; Welz, Cecilia; Duerr, Georg Daniel (The Thoracic and Cardiovascular Surgeon, 2019)
Background Crystalloid priming is a cost-effective, free from immunological reactions, and independent from human plasma delivery. However, there is some debate on the negative impact of low plasma colloid pressure and higher incidence of systemic inflammatory response syndrome (SIRS). The aim of the study was to rule out any adverse effects of crystalloid priming on the postoperative outcome.Methods We investigated 520 consecutive patients, including emergencies, who had isolated on-pump coronary artery bypass grafting in 2009 by retrospective analysis in our clinic. Crystalloid priming (n = 294) was introduced as an alternative to albumin (n = 226). Reviewing patient charts and IT-based data generated a dataset of perioperative parameters.Results There were no differences with respect to demographical data and preexisting comorbidities between both groups. Despite equal perfusion times, more volume had to be substituted during extracorporeal circulation following crystalloid priming. However, this did not influence the inhospital outcomes. According to the definition of the “Sepsis-3 Guidelines,” the incidence of SIRS was similar. There was no difference in the need for a vasopressor treatment, and only transient higher serum lactate levels were found in the crystalloid group. The incidence of neurologic and organ-related adverse events, as well as 30-day mortality was comparable.Conclusion The use of crystalloid priming is safe in coronary artery bypass grafting surgery in adults. However, there might be a greater need for crystalloid fluids during surgery.
Keywords: extracorporeal circulation priming; cardiopulmonary bypass; systemic inflammatory response syndrome; coronary artery bypass grafting; safety